E1.3 Healthcare professional's feedback about the clinical ethics rapid case review service of a specialist children's hospital. (4th October 2017) - Horne, A; Brierley, J; Aylett, SE
Abstract : Background: To evaluate the Clinical Ethics Service's (CES) Rapid Case Review Service (RCRS) at a specialist UK children's hospital. This confidential service, developed by the CES, discusses urgent ethical issues arising in the care of children in the hospital. Specific aims: Describe the spectrum of cases referred to the RCRS, evaluate the views of service users and consider the wider utility. Methods: 1. Case note review of referrals January 2012 – April 2016. 2. Questionnaire completed by 80 past service users. Results: 43 cases were reviewed (mean 7 years (0–18)). Diagnostic categories: Multiple organ failure (27%), Cancer (14%), Neurological (11%), Immunological (9%), Respiratory (7%) and Others (32%). 63% had 3 or more diagnoses. 91% had a life-limiting condition. Mean duration of admission at RCR was 3.2 months (0–12). 81% involved 2 or more specialties and 52% involved Palliative care. Referrers included: Critical care (25%); Cardiology (9%); Gastroenterology, Immunology and Neurology (7% each); Others (45%). 57% of ethical issues related to 'Experimental therapy' or 'Limitation and/or Withdrawal of Life-Sustaining Therapy'. Respondents praised the RCRS expertise and guidance, stated that all parties' views (including parental) were heard and felt that the ethical issues and child's best interests were fully addressed. 93% of respondents would recommend the RCRS, however, 56% thought service awareness insufficient. 51% felt inadequately prepared for the meeting whilst 69% completely followed RCRS recommendations. 62% thought other Trusts should be able to access this service; 88% thought other Trusts should provide their own service. Conclusion: The RCRS is viewed by clinician-users as compassionate and supportive of both clinicians and parents. It provides an effective way of peer reviewing ethical issues in a challenging healthcare environment and wider utility is suggested. Methods of improving RCRS awareness and a study ascertaining parents' views are planned.